Primate Population Dynamics Over 32.9 Years at Ngogo, Kibale National Park, Uganda - Lwanga, J.S.; Struhsaker, T.T.; Butynski, T.M.; Mitani, J.C. (American Journal of Primatology, 2011)
We present census data for eight primate species spanning 32.9 years along the same transect at Ngogo, Kibale National Park, Uganda, demonstrating major changes in the composition of the primate community. Correlated with an estimated decline of ∼89% in the red colobus population was an increase in encounter rates with chimpanzee parties. Our data, along with the unusually high rates of predation by chimpanzees on red colobus at Ngogo and the fact that the chimpanzee community at Ngogo is the largest ever recorded, support the conclusion that the red colobus decline was caused primarily by chimpanzee predation. This seems to be the first documented case of predation by one nonhuman primate causing the population decline in another. We evaluated disease and interspecific competition as other possible causes of the red colobus decline, but judged them to be relatively insignificant compared with predation by chimpanzees. Notable changes in encounter rates with other primate species may have resulted from forest expansion. Those for mangabeys, redtails, and black and white colobus increased significantly. Encounter rates increased for l'Hoest's monkeys too, but the increased sightings may have been an artifact of increased habituation. Sightings of blue monkey and baboon groups declined. There was no significant change in encounter rates for all species combined. The Ngogo primate community seemed to be in a nonequilibrium state, changing from one dominated by two species, a folivore (red colobus) and a frugivorous omnivore (redtails), to one dominated by three species of frugivorous omnivores (redtails, mangabeys, and chimpanzees). This study demonstrates the importance of long-term monitoring in understanding population dynamics and the role of intrinsic variables in shaping the species composition of a community.
Keywords: red colobus; chimpanzee predation; population dynamics; community ecology; Kibale National Park